Dynamic Fracture Tests Data Treatment Based on the Randomized Approach (Advances in Systems Science and Applications, 2017)
Methods of measurement and prediction of materials dynamic strength are complicated and not standardized. Usually dynamic tests are labour-consuming and each assay demands a lot of time in contrast to static experiments. The way of experimental data treatment based on incubation time criterion and randomized approach of sign-perturbed sums is considered. It is shown that a few experimental points are enough to determine strength parameter with accuracy proper for engineering. The lack of real experimental data is compensated in SPS-algorithm by carrying out a large number of virtual random tests in which the Bernulli signs are randomly generated in this method.